(untitled) - Borklund, Elmer (New York, 1977)
The book is an authoritative reference guide to the most important and influential 20th century critics in the English language. It included range from those who are also known for their creative writing to those who have made criticism a creative art on otself, from the great individualists and innovators of the inter-war years to contemporary critics still in mid-career.
Keywords: Literature; History and criticism